Inhabitatio, illuminatio, unio en studie i Luthers och den äldre lutherdomens teologi - Erikson, Leif (Åbo Akad., 1986)
Zusammenfassung.
Keywords: Luther, Martti; Rahtmann, Hermann -- 1585-1628; Luther, Martin -- 1483-1546; Arndt, Johann -- 1555-1621; Osiander, Andreas -- 1498-1552; Theologie